Hygric properties of porous building materials (VI): A round robin campaign. (November 2020) - Feng, Chi; Guimarães, Ana Sofia; Ramos, Nuno; Sun, Lixin; Gawin, Dariusz; Konca, Piotr; Hall, Christopher; Zhao, Jianhua; Hirsch, Hauke; Grunewald, John; Fredriksson, Maria; Hansen, Kurt Kielsgaard; et al.
Abstract: Hygric properties of porous building materials are important for hygrothermal analysis. Their experimental determination is however not always reliable, shown by the discrepant results from different laboratories on the same materials. In this study, a recent round robin campaign initiated by KU Leuven (Belgium) and participated in by eight institutes from different countries is reported. Ceramic brick was selected as the target material. The bulk density and open porosity from vacuum saturation tests, the capillary absorption coefficient and capillary moisture content from capillary absorption tests, and the vapor permeability from cup tests were measured. Results were analyzed statistically and compared with a previous round robin project, EC HAMSTAD. The reproducibility errors for determining the capillary absorption coefficient were noticeably reduced when compared with the EC HAMSTAD project, and the different laboratories in the present study obtained similar results from vacuum saturation tests and capillary absorption tests without a common protocol. For cup tests, large inter-laboratory discrepancies still exist. However, with a stringent common protocol different laboratories achieved consistent results. For all properties a common protocol did not change the average results of all laboratories. Highlights: Errors for measuring capillary absorption coefficient are much smaller than before. Vacuum saturation test and capillary absorption test do not need a common protocol. Large discrepancies still exist for cup test results from different labs. A stringent common protocol reduces the scatters for cup test in different labs. A common protocol does not change the mean value of all labs for studied properties.